Peptide-based Vaccines Derived from FcεRI Beta Subunit Can Reduce Allergic Response in Mice Model - Ahad Zare (Iranian Journal of Allergy, Asthma and Immunology, 2017)
Current therapeutic approaches in allergic diseases especially asthma generally focus on using immunological strategies. According to the importance of FceRI in controlling allergic response we used two extracellular regions of Fc epsilon receptor I (FceRI) beta subunit peptides to design two peptide-based vaccines. Probably these peptides vaccines by triggering the immune response to FceRI can reduce the allergic symptoms through blocking the IgE specific receptor. Two extracellular parts of FceRI beta subunit were made by peptide synthesizer and conjugated with keyhole limpet Hemocyanin. These conjugated peptides were used and evaluated as therapeutic vaccines in allergic airway inflammation mouse model. Total IgE and anti ovalbumin specific IgE were measured in mice serum and compared in vaccinated and unvaccinated allergic mice. Histamine, prostaglandin D2 (PGD2), IL-4 and IL-13 were measured in bronchoalveolar lavage (BAL) fluid of vaccinated allergic mice versus unvaccinated and histopathologic examination were performed in studied groups. After vaccination of mice with each of the peptide vaccines the specific antibodies titer increased significantly in vaccinated groups versus unvaccinated. In histopathologic study, lavage eosinophil percentage and peribronchial inflammation in lung sections of vaccinated groups was decreased (p<0.05). Also the allergic components including total IgE, anti ovalbumin specific IgE, histamine, PGD2, IL-4, and IL-13 showed substantial decline in vaccinated allergic mice.  Thus targeting the extracellular regions of FceRI beta subunit by peptide-based vaccines and induction of specific antibodies against them can reduce allergic responses in allergic mice model.